Peter Waldmann y Fernando Reinares (comp.). Sociedades en guerra civil. Conflictos violentos de Europa y América Latina. Barcelona, Paidós, 1999 - Giraldo Ramírez, Jorge (Estudios Políticos, 2000)
Reseña